The Impact of Human Resource Analytics on the Effectiveness of Human Resource Management at the Environmental Service Office of Southwest Papua Province - Roberthair Suripatty; Naomi Ormak; Victor P. K. Lengkong; Merinda H. Ch. Pandowo (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the effect of Human Resource Analytics on the effectiveness of human resource management at the Sorong Regency Environmental Service Office, with data-based decision making as an intervening variable. This research uses quantitative methods with an explanatory approach. The study population was all employees of the Environmental Service Office of Sorong Regency, Southwest Papua Province, which obtained a sample of 110 respondents with purposive sampling technique. Data were collected through a questionnaire with a Likert scale of 1-5, and analyzed using the Structural Equation Modeling Partial Least Square (SEM-PLS) method. The results showed that: (1) Human Resource Analytics has a positive and significant effect on HR management effectiveness; (2) Human Resource Analytics has a positive and significant effect on data-based decision making; (3) data-based decision making has a positive and significant effect on HR management effectiveness; and (4) Human Resource Analytics has an indirect effect on HR management effectiveness through data-based decision making as an intervening variable. These findings strengthen the evidence-based theory of HRM and confirm the importance of utilizing HR analytics to support the effectiveness of employee management in the public sector. .